Expression of liver X receptor-α in lesional and perilesional skin in patients with psoriasis vulgaris - Azza G.A Farag; Alaa H Maree; Rehab M Samaka; Mai A.A Zalata; Wafaa A Shehata (Wolters Kluwer Medknow Publications, 2021)
Background Psoriasis is a common chronic recurrent immune-mediated disease of the skin. Liver X receptor-alpha (LXR-α) is a member of the nuclear receptor family of transcription factors. LXR-α was found to be expressed in the skin. Objective To assess immunohistochemical expression of LXR-α in psoriatic (perilesional and perilesional) skin compared with control and to correlate its expression with the clinical and histopathological parameters of that disease in the studied patients. Patients and methods This case-control study was carried out on 76 participants, including 38 patients having chronic plaque psoriasis, besides 38 age-matched and sex-matched apparently normal volunteers (control group). The severity of psoriasis was assessed by Psoriasis Area and Severity Index score. The skin biopsies were subjected to hematoxylin and eosin and immunohistochemical staining of LXR-α. Results There was a significant stepladder downregulation of LXR-α from control to perilesional psoriatic skin, ending with lesional psoriatic skin, regarding its expression and H score in epidermis and dermal elements (P<0.001 for all). In the dermis, LXR-α topography was cytoplasmic in all psoriatic (perilesional and lesional) skin sections (100%) versus 22.2% in controls, where it was nucleocytoplasmic in 28 (77.8%) sections. Moreover, epidermal keratinocytes LXR-α demonstrated cytoplasmic localization in nearly all psoriatic sections (100% lesional and 90.9% perilesional) versus 18.9% controls (P<0.001). Conclusion Decreased LXR-α in psoriatic tissue may participate actively in psoriasis. LXR-α agonist may be of value in psoriasis management program.